Hedgehogs in Contact with Humans: Zoonotic and Reverse Zoonotic Transmission of Pathogens - Dražen Đuričić; Maja Lukač (Journal of Zoological and Botanical Gardens)
Numerous previous studies indicate that both wild hedgehogs and those kept as pets pose a significant risk to human health. At the same time, humans can also transmit various pathogens to hedgehogs (e.g., human herpesvirus 1). The risk of human infection from hedgehogs by various bacteria, viruses, fungi, rickettsiae, and parasites, and of hedgehog infection from humans, arises from close contact with pet hedgehogs, wild hedgehogs, and/or the contaminated environment which they cohabit with humans. People can also come into close contact with hedgehogs in city parks, rescue and rehabilitation centers, gardens, suburbs, and zoos. Numerous zoos keep different species of hedgehogs, which are often used for education and interaction with visitors, especially children. In spite of certain preventive measures, periodic examinations, and disease controls being carried out, the possibility of the transmission of infectious diseases from hedgehogs to visitors and employees is not excluded. Close contact poses a risk, especially if biosecurity is not properly maintained. The anthropological effects of coexistence, habitat sharing, and frequent human intrusion into hedgehog habitats have disrupted the natural relationship between humans and animals, and have led to an increase in the prevalence of various pathogens. Although many different pathogens have been isolated in hedgehogs, there is a need to study some of them in more detail and to understand their interaction and transmission possibilities, as well as zoonotic and reverse zoonotic pathogens.